The burden of hypertension in sub-Saharan Africa: a four-country cross sectional study - Guwatudde, David; Nankya-Mutyoba, Joan; Kalyesubula, Robert; Laurence, Carien; Adebamowo, Clement; Ajayi, IkeOluwapo; Bajunirwe, Francis; Njelekela, Marina; Chiwanga, Faraja S.; Reid, Todd; Volmink, Jimmy; Adami, Hans-Olov; et al. (BMC public health, 2015)
Hypertension, the leading single cause of morbidity and mortality worldwide, is a growing public health problem in sub-Saharan Africa (SSA). Few studies have estimated and compared the burden of hypertension across different SSA populations. We conducted a cross-sectional analysis of blood pressure data collected through a cohort study in four SSA countries, to estimate the prevalence of pre-hypertension, the prevalence of hypertension, and to identify the factors associated with hypertension. Methods: Participants were from five different population groups defined by occupation and degree of urbanization, including rural and peri-urban residents in Uganda, school teachers in South Africa and Tanzania, and nurses in Nigeria. We used a standardized questionnaire to collect data on demographic and behavioral characteristics, injuries, and history of diagnoses of chronic diseases and mental health. We also made physical measurements (weight, height and blood pressure), as well as biochemical measurements; which followed standardized protocols across the country sites. Modified Poison regression modelling was used to estimate prevalence ratios (PR) as measures of association between potential risk factors and hypertension. Results: The overall age-standardized prevalence of hypertension among the 1216 participants was 25.9 %. Prevalence was highest among nurses with an age-standardized prevalence (ASP) of 25.8 %, followed by school teachers (ASP = 23.2 %), peri-urban residents (ASP = 20.5 %) and lowest among rural residents (ASP = 8.7 %). Only 50.0 % of participants with hypertension were aware of their raised blood pressure. The overall age-standardized prevalence of pre-hypertension was 21.0 %. Factors found to be associated with hypertension were: population group, older age, higher body mass index, higher fasting plasma glucose level, lower level of education, and tobacco use.
Keywords: Prevalence of hypertension; Prevalence of pre-hypertension; Sub-Saharan Africa; Risk factors for hypertension; Chronic disease epidemiology